Write to return: The memoir of Hovhannes Cherishian and the restoration of the Armenian hearth. (October 2019) - Lessersohn, Nora
In this essay, I will analyze the memoir of Hovhannes Cherishian (1886–1967), an Ottoman Armenian shoemaker and genocide survivor from what is now southern Turkey, as an attempt to "restore the ruined ancestral [Armenian] hearth" and render "part of the lost legacy of [his] forebears" back unto "the possession of the Armenian community." By analyzing examples of transcultural memories from Cherishian's text, I will highlight the ways in which Cherishian uses his memoir to restore (and thus return to) a complex, multicultural, pre-genocide Ottoman Armenian existence. I will first locate Cherishian's memoir in nostalgia and memory studies as a way to draw out his role as an author. I will then explore aspects of Cherishian's text that reveal that which he lost to the genocide—and thus that which he restores through his memoir. In conclusion, I will discuss briefly the importance of memory sources for writing Ottoman and Armenian history.